Simple and Rapid Synthesis of Calcium Acetate from Scallop Shells to Reduce Environmental Issues - Montree Thongkam; Jinnaput Saelim; Banjong Boonchom; Somkiat Seesanong; Kittichai Chaiseeda; Nongnuch Laohavisuti; Kanokpon Bunya-atichart; Wimonmat Boonmee; Duangkamol Taemchuay (Adsorption Science & Technology)
The search for sustainable resources remains a subject of global interest. Calcium acetate used in many fields was prepared using waste scallop shell as a raw material, and its physicochemical properties were investigated. The waste scallop shells were transformed to calcium acetate compounds by reactions with four acetic acid concentrations at ambient temperature until the completely dried powder is obtained. The maximum yield of 87% with short reaction time at a low temperature was observed in the reaction of 60%w/w acetic acid with scallop shells. Thermal transformation reactions of all prepared calcium acetate samples revealed temperature conditions for heating to produce other advanced materials. FTIR and XRD results confirmed the purity and solid phase of all prepared calcium acetate samples, and they were compared with those of literatures and found to be well consistent. The obtained timber-like particles have different sizes depending on the acetic acid concentration. This work reports an easy and low-cost method with no environmental effect to produce cheap calcium products to be used in the industry.